Very high breakdown field strength for dielectric elastomer actuators quenched in dielectric liquid bath - La, Thanh-Giang (2014)
Dielectric elastomer actuators (DEAs) are prone to failure by pull-in instability. However, this work showed that DEAs, which were immersed in a silicone oil bath (Dow Corning Fluid 200 50cSt), can survive the pull-instability and operates beyond the pull-in voltage. Membrane DEAs (VHB 4905), which were pre-stretched bi-axially at 200% strain and immersed in the oil bath, survived a very high eld strength (>800 MV/m) and demonstrated areal strains up to 140%. The dielectric strength, achieved in the immersion, is approximately two times larger than that in the air (450 MV/m). This is achieved because the dielectric liquid bath helps to quench the localized electrical breakdown, which would have discharged sparks and burnt the dielectric lm in the air .